Burst-by-burst adaptive turbo-coded radial basis function-assisted decision feedback equalization. - Yee, M.S.
The performance of the proposed radial basis function (RBF) assisted turbo-coded adaptive modulation scheme is characterized in a wideband channel scenario. We commence by introducing the novel concept of the Jacobian RBF equalizer, which is a reduced-complexity version of the conventional RBF equalizer. Specifically, the Jacobian logarithmic RBF equalizer generates its output in the logarithmic domain and hence it can be used to provide soft outputs for the turbo-channel decoder. We propose using the average magnitude of the log-likelihood ratio (LLR) of the bits in the received transmission burst before channel decoding as the channel quality measure for controlling the mode-switching regime of our adaptive scheme
Keywords: BER performance; Jacobian RBF equalizer; Jacobian logarithmic RBF equalizer; Adaptive turbo-coded DFE; Burst-by-burst adaptive QAM; Channel decoding; Channel quality measure; Decision feedback equalization; Log-likelihood ratio; Mode-switching.; Quadrature amplitude modulation; Radial basis function-assisted DFE; Received transmission burst; Reduced-complexity equalizer; Soft outputs; Turbo-channel decoder; Turbo-coded adaptive modulation; Wideband channel